3-Amino-5-(indol-3-yl)methylene-4-oxo-2-thioxothiazolidine Derivatives as Antimicrobial Agents: Synthesis, Computational and Biological Evaluation - Volodymyr Horishny; Victor Kartsev; Vasyl Matiychuk; Athina Geronikaki; Petrou Anthi; Pavel Pogodin; Vladimir Poroikov; Marija Ivanov; Marina Kostic; Marina D. Soković; Phaedra Eleftheriou (MDPI AG, 2020)
Herein we report the design, synthesis, computational, and experimental evaluation of the antimicrobial activity of fourteen new 3-amino-5-(indol-3-yl) methylene-4-oxo-2-thioxothiazolidine derivatives. The structures were designed, and their antimicrobial activity and toxicity were predicted in silico. All synthesized compounds exhibited antibacterial activity against eight Gram-positive and Gram-negative bacteria. Their activity exceeded those of ampicillin and (for the majority of compounds) streptomycin. The most sensitive bacterium was S. aureus (American Type Culture Collection ATCC 6538), while L. monocytogenes (NCTC 7973) was the most resistant. The best antibacterial activity was observed for compound 5d (Z)-N-(5-((1H-indol-3-yl)methylene)-4-oxo-2-thioxothiazolidin-3-yl)-4-hydroxybenzamide (Minimal inhibitory concentration, MIC at 37.9-113.8 μM, and Minimal bactericidal concentration MBC at 57.8-118.3 μM). Three most active compounds 5d, 5g, and 5k being evaluated against three resistant strains, Methicillin resistant Staphilococcus aureus (MRSA), P. aeruginosa, and E. coli, were more potent against MRSA than ampicillin (MIC at 248-372 μM, MBC at 372-1240 μM). At the same time, streptomycin (MIC at 43-172 μM, MBC at 86-344 μM) did not show bactericidal activity at all. The compound 5d was also more active than ampicillin towards resistant P. aeruginosa strain. Antifungal activity of all compounds exceeded those of the reference antifungal agents bifonazole (MIC at 480-640 μM, and MFC at 640-800 μM) and ketoconazole (MIC 285-475 μM and MFC 380-950 μM). The best activity was exhibited by compound 5g. The most sensitive fungal was T. viride (IAM 5061), while A. fumigatus (human isolate) was the most resistant. Low cytotoxicity against HEK-293 human embryonic kidney cell line and reasonable selectivity indices were shown for the most active compounds 5d, 5g, 5k, 7c using thiazolyl blue tetrazolium bromide MTT assay. The docking studies indicated a probable involvement of E. coli Mur B inhibition in the antibacterial action, while CYP51 inhibition is likely responsible for the antifungal activity of the tested compounds.